SISTEM INFORMASI STAFF LOAN AND DOCUMENTATION (SLADU) PADA PT. BANK DBS INDONESIA - Anwar, Saiful; Yulia, Eka Rini (JIPETIK:Jurnal Ilmiah Penelitian Teknologi Informasi & Komputer, 2021)
It is undeniable that technological developments that occur at this time can help humans in doing their jobs much faster and easier. Currently, employees who work at Bank DBS Indonesia are given special loan facilities for employees with much lower interest rates than general loans, such as personal loans, home renovation loans, vehicle purchase loans and home ownership loans. At this time the process running on the team of staff loan and documentation PT Bank DBS Indonesia is still manual such as inputting staff loan data, searching for staff covenant documents if there are staff who want to make tax payments or take covenant documents, and reports to see which staff have not submitted the covenant document according to the deadline is still manual, causing delays in the company's performance and has not been fully able to meet the system needs desired by the company. With a computer-based information system, the loan data storage process will be neater, safer and also efficient, because the data will be stored in files on a computer that can be viewed again or printed when needed. Thus, the staff in theteam of loan and documentation PT. Bank DBS Indonesia can collect data on loan data for employees who have loans and view data and reports quickly, accurately and can be accounted for.